Jurisdiction agreements: exclusive, optional and asymmetrical. (2nd September 2015) - Keyes, Mary; Marshall, Brooke Adele
Abstract : The paradigm of the jurisdiction agreement designates a single, exclusive forum, allowing each party to determine, in advance of a dispute, the forum for litigation. The principles governing the enforcement of jurisdiction agreements are largely designed for this model. Some parties draft agreements that differ from this model, including agreements that purport to nominate multiple courts with "exclusive" jurisdiction, and unilateral optional agreements giving one party an option to select the forum after a dispute arises. These features raise the question of whether principles developed for the exclusive model regulate jurisdiction agreements that depart from it. This article explores the approach to exclusivity under the Hague Choice of Court Convention, the Brussels I Recast, and at common law. We demonstrate that non-uniquely "exclusive" and unilateral optional jurisdiction agreements are uncomfortably accommodated within and inconsistently treated by these regimes, comparing, particularly, the acceptance of unilateral optional agreements in England with their rejection in France.